2023
DOI: 10.1021/acssuschemeng.2c05552
|View full text |Cite
|
Sign up to set email alerts
|

Ring-Opening Copolymerization of Four-Dimensional Printable Polyesters Using Supramolecular Thiourea/Organocatalysis

Abstract: Ring-opening copolymerization (ROCOP) of polyesters may be used to achieve a wide variety of functional polymers using commercial monomer libraries, but primarily make use of metallic catalysts such as tin, magnesium, or cobalt complexes. However, the limitations of such catalysts include toxicity risks and environmental concerns for both the desired application, such as biomaterials, and the end-of-life consideration. There is a need for cleaner, friendlier, and less expensive routes to polymeric materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 52 publications
(94 reference statements)
0
25
0
Order By: Relevance
“…Limonene oxide was used to produce alternating polyester photocopolymers through a reaction with select cyclic anhydrides via ROCOP, specifically using phthalic anhydride (polyester - PHLO), cyclohexene anhydride (polyester - CHELO), cyclohexane anhydride (polyester - CHALO), and norbornene anhydride (polyester - NOLO) (Figure ). The reactions were conducted under open air conditions (no purification or N 2 ) at 100 °C for 24 h in toluene using the organobase 1,8-diazabicyclo[5.4.0]­undec-7-ene (DBU), a thiourea cocatalyst with a propargyl alcohol initiator, using a molar ratio of 200:200:1:1:0.1 (anhydride/epoxide/catalyst/cocatalyst/initiator), as previously described by Merckle et al The resultant polyesters displayed relatively low molecular weights (<5 kDa), not unexpected as sterically hindered epoxides, such as limonene oxide, are known to be less reactive compared with others. , For example, Nejad et al explored PHLO and limonene oxide with organobases, including 4-dimethylaminopyridine (DMAP), triazabicyclodecene (TBD), and bis­(triphenylphosphoranylidene)­ammonium chloride (PPNCL) as cocatalysts with salophen compounds, which resulted primarily in polyesters ranging from 3 kDa to nearly 5 kDa (1.3 < Đ < 1.5) . Peña Carrodeguas et al demonstrated PPNCL and DMAP with an iron complex to produce polyesters with M n up to 10.7 kDa, with dispersity less than 1.4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Limonene oxide was used to produce alternating polyester photocopolymers through a reaction with select cyclic anhydrides via ROCOP, specifically using phthalic anhydride (polyester - PHLO), cyclohexene anhydride (polyester - CHELO), cyclohexane anhydride (polyester - CHALO), and norbornene anhydride (polyester - NOLO) (Figure ). The reactions were conducted under open air conditions (no purification or N 2 ) at 100 °C for 24 h in toluene using the organobase 1,8-diazabicyclo[5.4.0]­undec-7-ene (DBU), a thiourea cocatalyst with a propargyl alcohol initiator, using a molar ratio of 200:200:1:1:0.1 (anhydride/epoxide/catalyst/cocatalyst/initiator), as previously described by Merckle et al The resultant polyesters displayed relatively low molecular weights (<5 kDa), not unexpected as sterically hindered epoxides, such as limonene oxide, are known to be less reactive compared with others. , For example, Nejad et al explored PHLO and limonene oxide with organobases, including 4-dimethylaminopyridine (DMAP), triazabicyclodecene (TBD), and bis­(triphenylphosphoranylidene)­ammonium chloride (PPNCL) as cocatalysts with salophen compounds, which resulted primarily in polyesters ranging from 3 kDa to nearly 5 kDa (1.3 < Đ < 1.5) . Peña Carrodeguas et al demonstrated PPNCL and DMAP with an iron complex to produce polyesters with M n up to 10.7 kDa, with dispersity less than 1.4 .…”
Section: Resultsmentioning
confidence: 99%
“…Vat photopolymerization 3D printing requires low viscosity for resin flow, and while nonreactive diluents are common, the use of reactive diluents prevents volumetric changes that lead to stress-induced cracking, as well as potentially further increasing the gelation rate. ,,, The reactive diluent used here was synthesized through the reaction of eugenol with methacryloyl chloride, thereby allowing for additional bioderived content with increasing diluent concentration. Importantly, this results in a methacrylate-containing reactive diluent moiety capable for propagating a radical for polymer formation by itself, as well as thiol–ene cross-linking, and while also possessing an allyl moiety suitable for thiol–ene cross-linking …”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] Thiol-ene crosslinking is an alternative gelation mechanism in vat photopolymerizations and 3D printing which provides greater reproducibility and lower variation in properties. 14,[19][20][21][22][23][24][25][26][27][28][29][30] Ring-opening copolymerization (ROCOP) of polyesters provides an opportunity to access photopolymers possessing the necessary functional groups, such as alkenes, necessary for thiol-ene photocrosslinking. The Coates, Darensbourg and Williams groups have been extremely successful, and prolific, with ROCOP for producing stereo-controlled, block, and functional polyesters, but the focus in these works has primarily been on metallic catalysts which are potentially risks for medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…62 Recently, Merckle et al demonstrated the use of functional thioureas co-catalysts with DBU to achieve up to nearly 50 kDa polyesters (Đ < 1.3) via ROCOP in open-air, bulk conditions, demonstrating a simple system with translational potential for various disciplines and industries due to the low barrier for implementation. 63 Importantly, the amine-functional thiourea co-catalyst incorporated into the polyester backbone, serving as an initiator for the ROCOP. 1 Control of dispersity has become a growing interest in multiple fields, and with many of the representative organocatalyst studies focusing on narrow molecular weight distributions and high molecular weights, there is an obvious gap in photopolymer material characterization that should be addressed: the role of dispersity in polyester photopolymer physical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation